Fatigue behavior and modeling of self-piercing riveted joints in aluminum alloy 6111. (July 2017) - Huang, Li; Guo, Haiding; Shi, Yandong; Huang, Shiyao; Su, Xuming
Highlights: The fatigue dangerous site of SPR coupons can be accurately predicted by the SWT parameter. Crack initiation life is found to be much longer than crack growth life from interrupted fatigue tests. A structural load based crack growth approach is proposed and successfully applied on the face cracking of SPR joint. Abstract: The fatigue behavior of self-piercing riveted (SPR) joints of aluminum alloy 6111-T4 has been experimentally and numerically investigated in current study. The dominant fatigue failure mode under tensile-shear (TS) loading is the corner crack at riveted hole with approximate quarter-elliptical crack front, and interrupted tests revealed that the crack growth life was much shorter than crack initiation life. A fatigue parameter, Smith-Watson-Topper (SWT) was proposed for crack initiation prediction in the 3D finite element analysis, while a structural load based crack growth approach was introduced for crack growth life estimation. Good agreement was found between predictions and experimental results.